Low Birth Weight Infants Outcome In Single Tertiary Referral Hospital - Putra, Dimas Abdi; I, Cininta N.; P, Wardhana M.; A, Aryananda R.; E, Gumilar K.; I, Aldika M.; B, Wicaksono; Ernawati, Ernawati; A, Sulistyono; Aditiawarman, Aditiawarman; J, Hermanto T.; N, Abdullah; G, Dachlan E. (UNUSA Press, 2019)
Background: Low birth weight (LBW) is defined by infants with birth weight less than 2500 gram, commonly caused by prematurity. Preterm infants are prone to problems such as organ immaturity, neurodevelopmental impairment until behavior disorder. Hypertension on pregnancy and preeclampsia is the most case referred and treated in dr. Soetomo General Hospital as a single tertiary teaching hospital in Surabaya, Indonesia which require early delivery and possess consequences to maternal and perinatal side. Objective: This study aims to determine the incidence and outcome of LBW infants born in dr. Soetomo General Hospital. Methods: Retrospective cross-sectional by using medical record data of dr. Soetomo General Hospital on January 2014 – December 2017. Results: There were 2350 infants with birth weight of 500-2499 gram, in which majority was on the range of 2001-2499 gram (38%.) Hypertension on pregnancy and the complications were the most indication for pregnancy termination that resulted in LBW infants. This study also found that the LBW outcome was linear with birth weight. In addition, the gestational age and five minutes APGAR score also had important role to the LBW outcome. Conclusion: The major cause of LBW infants in dr. Soetomo General Hospital was hypertension on pregnancy. There was a positive trend of survival in infants with birth weight range of 1501-2000 gram.